Ethical Implications and Challenges of AI Implementation in Business Operations - Ahmad Nur Ihsan Purwanto; Muhammad Fauzan; Tiara Widya; Nabiel Syarof Azzaky (TechComp Innovations: Journal of Computer Science and Technology, 2024)
This study explores the ethical implications and challenges associated with the implementation of artificial intelligence (AI) in business operations. The research aims to identify key ethical concerns, such as data privacy, algorithmic bias, and workforce displacement, while analyzing their impact on organizational practices and stakeholder trust. Utilizing a library research approach, the study synthesizes insights from academic literature, industry reports, and case studies to examine the intersection of AI ethics and business performance. The findings highlight the need for transparent governance frameworks, inclusive algorithm design, and ethical AI policies to address these challenges effectively. The research underscores the importance of balancing technological innovation with ethical considerations, offering practical implications for businesses seeking to integrate AI responsibly into their operations